"The pandemic made us stop and think about who we are and what we want:" Using intersectionality to understand migrant and refugee women's experiences of gender-based violence during COVID-19 - Alli Gillespie; Ilana Seff; Camilla Caron; Maria Margherita Maglietti; Dorcas Erskine; Catherine Poulton; Lindsay Stark (BMC, 2022)
Abstract Background Migrant and refugee women have faced a myriad of challenges during COVID-19, which are often exacerbated by the interaction between this population's diverse identities and established systems in the local context. This qualitative study uses the lens of intersectionality to understand migrant and refugee women's experiences of gender-based violence and access to and quality of support services in Italy during the first year of COVID-19. Methods Data were gathered from 51 key informant interviews and eight focus group discussions of 31 participants. Key informants included service providers across sectors, including gender-based violence and anti-violence organizations, government and law, health, psychology, social work, and anti-trafficking administration. Focus group participants were migrant and refugee women aged 18-65 from the following countries of origin: Bangladesh, Cameroon, Colombia, El Salvador, Gambia, Ghana, Honduras, Libya, Nigeria, Pakistan, Peru, Senegal, and Syria. Interviews were audio-recorded, transcribed and coded using a collaborative process with partners from UNICEF. Transcripts were then evaluated for arising themes using three methods of intersectionality analysis. Results Data analysis revealed how COVID-19 converged with sexism, racism, and xenophobia in Italy, leading to increased public and domestic violence against refugee and migrant women. Another prominent theme was the exacerbated vulnerability for refugee and migrant women in precarious socioeconomic situations, which prompted many service providers to recognize and address gaps in service offerings and coordination around basic needs. However, due to resource constraints and bias, providers did not systematically incorporate inclusive language and cultural mediation into remote and online services, creating a heightened barrier to access for non-Italian women despite their complex needs. As such, refugee and migrant women highlighted community-based solidarity and support as protective factors during lockdown periods. Conclusion Findings emphasize how overlapping dominant sociocultural and socioeconomic systems impacted refugee and migrant women's experiences of violence during COVID-19 in Italy, and how some support services were unprepared to respond to the complex needs of diverse, newcomer populations. We discuss how policymakers and practitioners might consider intersectionality in their preparedness and response planning for gender-based violence services during health emergencies moving forward.